Technical, financial and institutional feasibility assessment of DNA fingerprinting for varietal monitoring - CGIAR Research Program on Maize (2019)
The study provides a comprehensive business plan analysis of DNA fingerprinting for a developing country. The study is completed and part of the recommendations are being implemented by our national partners.